Universal scaling laws in surface water bodies and their zones of influence - Sagar, B. S. Daya (AMER GEOPHYSICAL UNION, 2007)
[1] Topologically, water bodies are the first-level topographic regions that get flooded, and as the flood level gets higher, adjacent water bodies merge. The looplike network that forms along all these merging points represents zones of influence of each water body. These two topologically interdependent phenomena follow the universal scaling laws similar to certain other environmental and biological phenomena. Despite morphological variations, water bodies and their influence zones of varied sizes and shapes have different sets of scaling exponents, thereby determining that they belong to different universality classes.